Impact of Russian Ukrainian war on commodity trade - Busheev, Artemii; Štěrbová, Ludmila, 1957-; Bolotov, Ilya; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
This thesis is devoted to the analysis of the impact of the modern Russian-Ukrainian war on international trade in key commodities – grain, oil, and gas. The focus is on Russia's strategies to overcome Western sanctions, including redirecting commodity flows through third countries (Kazakhstan, Turkey, China, and India) and using alternative logistics schemes. Based on a mixed methodology (quantitative analysis of trade data and qualitative assessment of policy decisions), the work demonstrates that, despite the sanctions, Russia has maintained significant exports, especially to Asian markets, albeit with financial losses due to discounts and additional costs. At the same time, the war has led to structural changes in global supply chains: a reduction in Russian gas supplies to Europe has accelerated the transition to LNG, and the grain crisis has forced countries to look for alternative suppliers.
Vedoucí práce: Ludmila Štěrbová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: international and diplomatic studies [obor dipl. práce]; diplomové práce; master's theses